Penyelesaian Pembiayaan Bermasalah Pada PT. Bank Nagari Cabang Simpang Empat - Siti Fadilah; Fajar Budiman; Yossi Eriawati (Universitas 45 Surabaya, 2023)
The background in this research is the problematic financing that occurred at PT. Bank Nagari Simpang Empat Branch. Not all of the financing provided to customers can be returned properly and does not bring the expected benefits. This study aims to see and analyze problem financing at PT. Bank Nagari Simpang Empat Branch. This study uses field research methods, the type of approach is qualitative. The data source for this research is the Leaders and Employees of PT. Bank Nagari, Simpang Empat Pasaman Barat Branch. The data collected in this study are primary data and secondary data. This primary data was obtained through interviews with informants, namely PT Bank Nagari Simpang Empat Branch. The results of the study show that in the steps taken by PT. Bank Nagari Simpang Empat Branch, when a customer is unable to pay a financing installment or when a financing problem occurs, the bank will give a warning letter 3 (three) times, if the customer has good faith and If you are able to pay arrears then it can be done with Restructuring. If the customer is unable to pay the arrears, the Bank will conduct a Collateral Auction. Basically non-performing financing is a risk that often occurs in the banking world. However, what is important in this problem is how the banking sector can overcome and resolve this so that unwanted things do not occur and do not harm the bank.